2022
DOI: 10.1021/acsaem.2c01558
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Hydrogen Atom Modified PdPt Nanosheets for Efficient Ethanol Electro-oxidation with High C–C Bond Cleavage Selectivity

Abstract: Direct ethanol fuel cells (DEFCs) are a type of promising portable power source with low environmental pollution and high energy density. However, the further commercialization of DEFCs is hindered by the incomplete oxidation of ethanol on the electrocatalysts. Herein, we report a successful synthesis of ultrathin PdPtH nanosheets (NSs) for the first time by the in situ formation of interstitial hydrogen atoms accompanied by wet-chemical coreduction of Pd and Pt precursors. The PdPtH NSs possess selectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In ethanol oxidation, with the increase of voltage, the intensity of consumption of ethanol and OH – is more obvious, and more acetate is produced (Figure a). The band at 1348 cm –1 is the stretching vibration of the methyl group in acetate, while the bands at 1413 and 1550 cm –1 belong to the symmetric and antisymmetric stretching of the C–O bond in the acetate. The peak intensity at 1413 cm –1 is stronger than that at 1550 cm –1 , which is due to the superposition with carbonate at approximately 1390 cm –1 , and carbon dioxide (CO 2 ) can be detected at 2345 cm –1 at 1.1 V, indicating that the C–C bond in ethanol is broken (Figure d) (CH 3 CH 2 OH – 12e – + 16OH – → 2CO 3 2– + 11 H 2 O). In EGOR, PdPtBiTe/C detects signals from low potential at 0.4 V, which is consistent with the fast dynamics in Figure b. The bands at 1076, 1238, 1326, and 1575 cm –1 are attributed to glycolate.…”
Section: Resultsmentioning
confidence: 99%
“…In ethanol oxidation, with the increase of voltage, the intensity of consumption of ethanol and OH – is more obvious, and more acetate is produced (Figure a). The band at 1348 cm –1 is the stretching vibration of the methyl group in acetate, while the bands at 1413 and 1550 cm –1 belong to the symmetric and antisymmetric stretching of the C–O bond in the acetate. The peak intensity at 1413 cm –1 is stronger than that at 1550 cm –1 , which is due to the superposition with carbonate at approximately 1390 cm –1 , and carbon dioxide (CO 2 ) can be detected at 2345 cm –1 at 1.1 V, indicating that the C–C bond in ethanol is broken (Figure d) (CH 3 CH 2 OH – 12e – + 16OH – → 2CO 3 2– + 11 H 2 O). In EGOR, PdPtBiTe/C detects signals from low potential at 0.4 V, which is consistent with the fast dynamics in Figure b. The bands at 1076, 1238, 1326, and 1575 cm –1 are attributed to glycolate.…”
Section: Resultsmentioning
confidence: 99%
“…4). 59 The PdPtH nanosheets show a high selectivity of 15.1% related to C–C bond splitting for the EOR to CO 2 through the C1 pathway at a low potential.…”
Section: Applications Of H Intercalated Pd-based Nanocatalysts For El...mentioning
confidence: 96%
“…[48][49][50][51] In recent years, modifying the electronic structure of Pd has paved another pathway for substantially enhancing their electrocatalytic performance. [52][53][54][55][56][57][58][59][60] Incorporating H atoms into Pd lattice can tailor the d-band center of Pd and accelerate the reaction kinetics by weakening the bond between the catalyst and reaction intermediate. 61,62 Kabiraz and coworkers have demonstrated that β-PdH cubes and octahedra could deliver enhanced catalytic activity and stability for MOR, due to the ligand effect originating from the interstitial alloying of β-PdH.…”
Section: Electrocatalytic Alcohol Oxidation Reactionmentioning
confidence: 99%
“…4 It is now generally accepted that electrochemical ethanol oxidation reaction (EOR) might follow a dual-pathway mechanism, including the C 1 reaction pathway with complete ethanol oxidation and the C 2 route with the preservation of the C-C bond. [5][6][7] The C 1 pathway involves a 12-electron transfer per molecular unit, which is preferred in improving the energy density of direct ethanol fuel cells (DEFCs). [8][9][10] However, the commercialization of DEFCs still faces some challenges: (1) the cleavage of the C-C bond requires noble metal catalysts such as Rh and Pt/Rh/SnO 2 , 11,12 Rh can even dissociate the C-C bond at open circuit potential in an alkaline solution.…”
Section: Introductionmentioning
confidence: 99%